Exploration of the power-performance tradeoff through parameterization of FPGA-based multiprocessor systems - Göhringer, Diana (2011)
The design space of FPGA-based processor systems is huge, because many parameters can be modified at design- and runtime to achieve an efficient system solution in terms of performance, power and energy consumption. Such parameters are, for example, the number of processors and their configurations, the clock frequencies at design time, the use of dynamic frequency scaling at runtime, the application task distribution, and the FPGA type and size. The major contribution of this paper is the exploration of all these parameters and their impact on performance, power dissipation, and energy consumption for four different application scenarios. The goal is to introduce a first approach for a developer's guideline, supporting the choice of an optimized and specific system parameterization for a target application on FPGA-based multiprocessor systems-on-chip. The FPGAs used for these explorations were Xilinx Virtex-4 and Xilinx Virtex-5. The performance results were measured on the FPGA while the power consumption was estimated using the Xilinx X Power Analyzer tool. Finally, a novel runtime adaptive multiprocessor architecture for dynamic clock frequency scaling is introduced and used for the performance, power and energy consumption evaluations.